Shortcuts to adiabaticity for trapped ultracold gases - Schaff, Jean-François (2011)
We study experimentally and theoretically the controlled transfer f harmonically trapped ultracold gases between different quantum states. n particular, we experimentally demonstrate a fast decompression anddisplacement of both a non-interacting gas and an interacting Bose-Einstein ondensate, which are initially at equilibrium. The decompression parameters re engineered such that the final state is identical to that obtained after a erfectly adiabatic transformation despite the fact that the fast decompression is erformed in the strongly non-adiabatic regime. During the transfer the atomic ample goes through strongly out-of-equilibrium states, while the external onfinement is modified until the system reaches the desired stationary state. The cheme is theoretically based on the invariants of motion and scaling equation echniques and can be generalized to decompression trajectories including an rbitrary deformation of the trap. It is also directly applicable to arbitrary initial on-equilibrium states. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.